2018
DOI: 10.1136/bcr-2017-223459
|View full text |Cite
|
Sign up to set email alerts
|

Carpal synovitis with capitate bone tuberculosis in a child

Abstract: We present a 10-year-old boy with 2-month duration non-traumatic wrist pain and inflammatory signs. Due to elevated inflammatory markers on blood tests, with an increase in radiocarpal and intercarpal joints synovial fluid and no bony lesions, the patient was submitted to wrist arthrocentesis for the suspicion of septic arthritis. The patient did not improve on conventional treatment, however. An MRI showed synovitis around the carpus and a lytic lesion of the capitate bone due to osteomyelitis. A biopsy was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Instrumented surgeries were only performed in 3 (23.1 %) patients: one had a total L1 collapse, instability and lumbar lordosis rectification, with lumbar canal stenosis; another had Frankel grade B neurological deficit and the goal was to achieve in situ fixation to prevent clinical deterioration; and the third had a two-vertebrae collapse and canal stenosis. The two patients with ESTB who were submitted to surgery were a 17-year-old boy born in Angola with a 2-month prosthetic hip infection that underwent spacer removal and debridement [17] and a 10-year-old boy with a chronic wrist effusion and capitate osteomyelitis, submitted to multiple drainages [16], both cases previously reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrumented surgeries were only performed in 3 (23.1 %) patients: one had a total L1 collapse, instability and lumbar lordosis rectification, with lumbar canal stenosis; another had Frankel grade B neurological deficit and the goal was to achieve in situ fixation to prevent clinical deterioration; and the third had a two-vertebrae collapse and canal stenosis. The two patients with ESTB who were submitted to surgery were a 17-year-old boy born in Angola with a 2-month prosthetic hip infection that underwent spacer removal and debridement [17] and a 10-year-old boy with a chronic wrist effusion and capitate osteomyelitis, submitted to multiple drainages [16], both cases previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…One (5.6 %) did not receive ethambutol and completed the triple ATT scheme and in three (16.7 %) isoniazid was replaced by levofloxacin due to isoniazid resistance (n=2, 11.1 %) or hepatic toxicity (n=1, 5.6 %). The two patients with ESTB who were submitted to surgery were a 17-year-old boy born in Angola with a 2-month prosthetic hip infection that underwent spacer removal and debridement [17] and a 10-year-old boy with a chronic wrist effusion and capitate osteomyelitis, submitted to multiple drainages [16], both cases previously reported.…”
Section: Treatmentmentioning
confidence: 99%
“…Prakash and Mehtani [7] reported isolated involvement of the scaphoid bone. In 2018, Grenho et al [8] also reported isolated involvement of the capitate with carpal synovitis. All the abovementioned cases had restriction of wrist and hand function with involvement of the adjacent intercarpal joints.…”
Section: Discussionmentioning
confidence: 99%
“…Common sites of primary osseous focus are the os capitatum or distal end of the radius [2]. Very few cases have been reported of isolated involvement of a single bone or joint in the wrist or hand [3][4][5][6][7][8]. Isolated involvement of the hamate, in particular, is even rarer.…”
Section: Introductionmentioning
confidence: 99%
“…Prakash reported a case with involvement of capitate in a 12-year-old boy who also healed with ATT given for 1 year and did not show recurrence at 18 months of follow-up 9. Grenho et al reported a similar case of capitate infection in a 10-year-old boy with good outcome 10…”
Section: Discussionmentioning
confidence: 99%